(untitled) (Current Horticulture, 2024)
Bael (Aegle marmelos) ’Thar Srishti’ was identified and released in 2020 by ICAR-CIAH, Bikaner, Rajasthan. It is first variety with highly centric seed cavity (locule arrangement) with attractive pulp and appealing ripened fruit colour having no off flavour. Its average yield/tree during 9th year (91.50 kg), fruit weight (1.55), fruit size (21.00 × 14.00 cm), fruit girth (43.53 cm), shell thickness (0.20cm), number of locules in cross section (14.00), peel weight (200.00 g), pulp weight (1.20 kg), fibre weight (62.32 g), total seed weight (19.00 g), total number of seed/fruit (98.15),TSS of pulp (36.75°brix), TSS of mucilage (51.50°brix),total sugar(21.40%), acidity (0.35%) and TSS/acidity ratio(128.33) were recorded under rainfed semi-arid conditions of western India. Belonging to mid maturity group (April), its fruit attain maximum size up to 20th October. Its fruits are comparatively less affected (18.13%) by sunscald due to dense canopy and lustrous and luxuriant growth with peculiar leaves. Colour of pulp is deep yellow after ripening and emits very less aroma. Fully mature fruits can be kept for 10-15 days and ripe ones for 7-9 days under ambient condition.